GnRH agonist trigger versus hCG trigger in GnRH antagonist in IVF/ICSI cycles: A review article - Ashraf Alyasin; Shayesteh Mehdinejadiani; Candidate. Marzieh Ghasemi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Routinely, a bolus of 5.000-10.000 IU human chorionic gonadotropin (hCG) is used for the final follicular maturation and ovulation as a standard method. HCG has the same effect of luteinizing hormone (LH) with long half-life. It has the long lutheotrophic effect which increases the risk of ovarian hyper stimulation syndrome (OHSS). Recently, gonadotropin-releasing hormone agonist (GnRH-a) trigger has been used for the induction of final follicular maturation and ovulation with the aim of reducing the OHSS risk. Several studies have shown that the releases of endogenous follicular stimulating hormone (FSH) and LH after administration of GnRH agonist in in vitro fertilization (IVF) cycles are able to precede the final follicular maturation leading to removal of fertile oocyte with normal development of the embryo and ultimately pregnancy. But based on the results of some studies, using GnRH-a trigger leads to defect luteal-phase resulting to reduce the implantation and clinical pregnancy rates and also increase abortion in fresh embryo transfer cycles compared to routine IVF cycle with hCG triggering . Also, in recent years, studies have continued to modify the luteal phase support, so that the fresh embryo transfer is possible too. In this review, we examined the benefits, problems, and also ways to reform GnRH agonist triggering complications.